Modeling and Forecasting Mortality Rates : A Comparative Study with the Lee-Carter Stochastic Model - Smeed, Andrew (My University, 2015)
This project examines the performance of the Lee-Carter model on data from selected countries in North America (Canada and USA) and Eastern Europe. We use the Singular Value Decomposition (SVD) and the Maximum Likelihood (MLE) methods.
Color poster with text, graphs, and images.
Keywords: Demographics; Lee-Carter model; Longetivity; Mortality rates; Posters